Epidermal bladder cells confer salinity stress tolerance in the halophyte quinoa and Atriplex species. (18th July 2017) - Kiani‐Pouya, Ali; Roessner, Ute; Jayasinghe, Nirupama S.; Lutz, Adrian; Rupasinghe, Thusitha; Bazihizina, Nadia; Bohm, Jennifer; Alharbi, Sulaiman; Hedrich, Rainer; Shabala, Sergey
Abstract: Epidermal bladder cells (EBCs) have been postulated to assist halophytes in coping with saline environments. However, little direct supporting evidence is available. Here, Chenopodium quinoa plants were grown under saline conditions for 5 weeks. One day prior to salinity treatment, EBCs from all leaves and petioles were gently removed by using a soft cosmetic brush and physiological, ionic and metabolic changes in brushed and non‐brushed leaves were compared. Gentle removal of EBC neither initiated wound metabolism nor affected the physiology and biochemistry of control‐grown plants but did have a pronounced effect on salt‐grown plants, resulting in a salt‐sensitive phenotype. Of 91 detected metabolites, more than half were significantly affected by salinity. Removal of EBC dramatically modified these metabolic changes, with the biggest differences reported for gamma‐aminobutyric acid (GABA), proline, sucrose and inositol, affecting ion transport across cellular membranes (as shown in electrophysiological experiments). This work provides the first direct evidence for a role of EBC in salt tolerance in halophytes and attributes this to (1) a key role of EBC as a salt dump for external sequestration of sodium; (2) improved K + retention in leaf mesophyll and (3) EBC as a storage space for several metabolites known to modulate plant ionic relations. Abstract : Epidermal bladder cells (EBCs) have been postulated to assist halophytes in coping with saline environments; however, no direct evidence was provided until now. In this work, we show that the gentle removal of EBC results in a salt‐sensitive phenotype and attribute this phenomenon to a key role of EBC as a salt dump and a storage space for several metabolites known to modulate plant ionic relations.